2011
DOI: 10.1007/s11250-011-9876-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for subclinical coccidiosis in broiler chicken farms in Mazandaran province, Iran

Abstract: Coccidiosis is a disease of almost universal importance in Poultry production. The subclinical form of coccidiosis has most significant economic impact due to impaired growth rate and feed conversion. Some factors such as: age, size of flock, season, etc., may effect on severity of this disease. In this study, the relationships between some major risk factors and prevalence of subclinical coccidiosis were investigated. This study was done in 120 broiler farms in five different cities of Mazandaran province, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 12 publications
(11 reference statements)
4
33
3
3
Order By: Relevance
“…These authors reported that E. tenella is the most prevalent species in Africa, Middle East and Asia. However, disagrees with who reported E. acervulina was the most prevalent species in Iran as in Europe, Australia and North America [27]. The present study observed high prevalence of Eimeria spp.…”
Section: Discussioncontrasting
confidence: 99%
“…These authors reported that E. tenella is the most prevalent species in Africa, Middle East and Asia. However, disagrees with who reported E. acervulina was the most prevalent species in Iran as in Europe, Australia and North America [27]. The present study observed high prevalence of Eimeria spp.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, in a study with chickens raised on used litter in the USA, the predominant species were E. acervulina , E. maxima , E. praecox and E. tenella , according to Lee et al [25]. In Africa, Middle East and Asia the most frequent species reported in broilers are E. brunetti (between 10 and 60%) and E. necatrix (4–30%) [1, 4, 24, 26, 44]. In the same geographical areas, E. tenella was the most prevalent species [4, 24], except in Iran where as in Europe, Australia and North America the most prevalent species was E. acervulina [44].…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the coccidiostats have become less effective due to development of drug resistance. Drug-resistant Eimeria strains are responsible for subclinical coccidiosis and, subsequently, for impaired economical performance as body weight gain, and feed conversion ratio [44]. The economic losses are significant, being estimated at more than 3 billion US$ annually in the world [11], and the economic importance of subclinical coccidiosis varies with composition of coccidial populations [16].…”
Section: Introductionmentioning
confidence: 99%
“…Management strategies which disrupt the eimerian faecal-oral lifecycle, such as housing poultry on raised wired floors, reduce Eimeria occurrence and outbreaks of disease (Lunden et al, 2000). Chicken breed and age at slaughter also influence Eimeria occurrence (Bumstead and Millard, 1992, Shirzad et al, 2011). The occurrence of coccidiosis can also vary due to climatic conditions, with evidence of elevated parasite levels and disease during wetter and warmer seasons (Awais et al, 2012, Jatau et al, 2012, Luu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%